一种求解含区间参数复合材料结构静力学响应的径向基神经网络配点方法 (2022)
本发明公开了一种求解含区间参数复合材料结构静力学响应的径向基神经网络配点方法。该方法首先在复合材料结构参数区间域内选择一系列样本点，并使用有限元的方法求解这些样本点的结构静力学响应值。将这些数据作为径向基神经网络的训练样本。根据样本点的数目选择神经网络隐藏层中径向基函数的数量，再用K均值算法得到各个径向基函数的中心值，然后再用递归最小二乘方法得神经网络隐藏层和输出层之间的权值。将训练好的径向基神经网络作为原结构响应函数的近似响应函数。再利用遗传算法求解径向基神经网络的最大和最小值作为含区间参数的复合材料结构静力学响应的上界和下界。 The invention discloses a radial-basis-neural-network point allocation method of solving statics response of a composite material structure containing interval parameters. According to the method, firstly, a series of sample points are selected in a parameter interval domain of the composite material structure, and a finite-element method is used to solve structure statics response values of the sample points; the data are used as training samples of a radial-basis neural-network; the number of radial basis functions in a hidden layer of the neural network is selected according to the number of the sample points, then a K-means algorithm is used to obtain a center value of each radial basis function, and then a recursive least square method is u